The Readiness of Palm Oil Industry in Enterprise Resource Planning - Darius Antoni; Deni Fikari; Muhamad Akbar; Ferry Jie (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
The palm oil industry is one of the sources of non-oil and gas foreign exchange of Indonesia. It contributes to National Gross Domestic Product at 13.96% in 2017. This study aims to examine the readiness of palm oil industry in the implementation of Enterprise Resources Planning (ERP). The readiness of palm oil industry in implementing ERP, is not only about a large cost, but also the ERP has required great resources including human respurces, technology, management, and process and data. Thus, it should fit the needs of the industry. Using the Critical Success Factors (CSF) method, this study employs five dimensions of the ERP readiness, that is management, process, technology, data, and personnel. A survey research method is employed to acquire the data and there are 19 items for those five dimensions. A gap analysis is employed to analyse the data and this method is used to determinethe disparity between existing conditions and future expectations. The findings reveal that the palm oil industry is well prepared to implement the ERP from four dimensions of management, technology, process and personnel.The management factor is the one of an factor of readiness in the ready category together with other factors including process, and human resources. Technology is the best factor which has led to increasing demands for building a strong information technology infrastructure to integrate business processes. The company needs to complete the master data onto the database and change the database system integrated into a single database that causes data is lack of ready data in ERP implementation.